Use of reminder box for the amount of iron tablet consumption in pregnant women - Nurbaiti Nurbaiti (AcTion: Aceh Nutrition Journal, 2023)
One of the health issues affecting pregnant women in Indonesia is iron deficiency anemia. Iron tablet supplementation is used to manage anemia, but this program has not been successful because of low compliance from forgetfulness. The use of a reminder can increase the amount of iron pill consumption. This study aimed to determine how much iron pill ingestion was impacted by the reminder box. This kind of research uses a post-test-only control group, which has a quasi-experimental design. Sixty respondents were divided into 30 intervention groups and 30 control groups. The intervention group received iron tablets in a box marked with the day, date, and time as a reminder to take their prescription, while the control group received theirs in plastic. Both groups were observed for 30 days, recording their observations on a monitoring form. An impartial t-test was utilized in the data analysis. The average amount of iron tablets ingested did not differ between the intervention and control groups (p= 0,417), although the intervention group consumed more than the average amount. Reminder boxes enhance consumption, but additional proof is required. It is unclear whether placing reminders where they are simple to notice and access will impact compliance.